Miss Julia stirs up trouble [large type] - Ross, Ann B. (Ross, Ann B. Miss Julia series., 2013)
When domestically challenged Hazel Marie is forced to take over the care of her household in the wake of a housekeeper's injury, Miss Julia rallies the ladies of Abbotsville to provide cooking lessons only to confront Hazel Marie's reprobate uncle, who harbors a suspicious agenda.